2008
DOI: 10.1021/ja802788g
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Structure of a Minimal Nucleic Acid

Abstract: The crystal structure of an 8-mer (S)-GNA duplex is presented. As a tool for phasing, the anomalous diffraction of two copper(II) ions within two artificial metallo-base pairs was employed. The duplex structure confirms a canonical Watson−Crick base pairing scheme of GNA with antiparallel strands. The duplex secondary structure is distinct from canonical A- and B-form nucleic acids and can be described as a right-handed helical ribbon wrapped around the helix axis, resulting in a large hollow core. Most intrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(142 citation statements)
references
References 16 publications
2
137
1
2
Order By: Relevance
“…The monohydrogen phosphate bridges the cyclo-O8-Na + with the sperminium cation, and the cyclo-O8-Na + has an inverted alternating orientation ( Figure 3A). Interestingly, the sperminium tetracation cannot bind alone to DNA in this model, since the distances [d (N 1 ,N 4 ) = 490 pm; d (N 4 ,N 9 ) = 620 pm; d (N 1 ,N 12 ) = 1,600 pm] between the four ammonium nitrogens do not fit the intrastrand phosphate-phosphate distance of dsDNA (B-DNA: dØ = 700 pm [36,37]; A-DNA: dØ = 590-600 pm [37][38][39][40]; Z-DNA: dØ = 590 pm (step pCp), dØ = 600 pm (step pGp) [40]). Therefore, it is quite remarkable that in our model for the first epigenetic shell of in vivo DNA ( Figure 3A) a repeating unit is formed from cyclo-O8-Na + and spermine phosphate that perfectly fits both the triplet nature of the genetic code [41] and the repeating distance of the phosphate anion backbone of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The monohydrogen phosphate bridges the cyclo-O8-Na + with the sperminium cation, and the cyclo-O8-Na + has an inverted alternating orientation ( Figure 3A). Interestingly, the sperminium tetracation cannot bind alone to DNA in this model, since the distances [d (N 1 ,N 4 ) = 490 pm; d (N 4 ,N 9 ) = 620 pm; d (N 1 ,N 12 ) = 1,600 pm] between the four ammonium nitrogens do not fit the intrastrand phosphate-phosphate distance of dsDNA (B-DNA: dØ = 700 pm [36,37]; A-DNA: dØ = 590-600 pm [37][38][39][40]; Z-DNA: dØ = 590 pm (step pCp), dØ = 600 pm (step pGp) [40]). Therefore, it is quite remarkable that in our model for the first epigenetic shell of in vivo DNA ( Figure 3A) a repeating unit is formed from cyclo-O8-Na + and spermine phosphate that perfectly fits both the triplet nature of the genetic code [41] and the repeating distance of the phosphate anion backbone of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster cations of heptoxazocan-8-ium -octoxocane -Na 35 Cl (1:2:m) (m = 0-6) were observed, together with characteristic +2 isotope peaks resulting from substitution of one 37 Cl for 35 Cl (m = 1-6), and together with -2 peaks of heptoxazocan-8-iumyl -octoxocane (1:2) cluster radical cations (m = 0-6) ( Figure 5). Clusters of [(cytidine)2 + Na + (NaCl)n] + (n = 0-5) were also observed ( Figure 5).…”
Section: Catalase Assay Of Nc and Candida Utilis Rna -Biomimetic Syntmentioning
confidence: 99%
“…The cluster cations of heptoxazocan-8-ium -octoxocane -Na 35 Cl (1:2:m) are marked (m = 0-6). Not marked are the +2 isotope peaks resulting from 37 Cl instead of one 35 Cl (m = 1-6). The origin of the heptoxazocan-8-iumyl -octoxocane (1:2) cluster radical cations (-2 peaks) is indicated in the inset.…”
Section: Catalase Assay Of Nc and Candida Utilis Rna -Biomimetic Syntmentioning
confidence: 99%
“…Also interesting to note is that the HCu II H base pair was additionally incorporated into a glycol nucleic acid (GNA). 71,72 Single-crystal X-ray diffraction analysis of the metallo-GNA duplex revealed that two H nucleobases coordinated to the central Cu 2+ ion in a square-planar fashion with only a slight propeller twist (ca. 15°).…”
Section: Cu(ii)-mediated Base Pairingmentioning
confidence: 99%